RETAIL CUSTOMERS’ PREFERENCE TOWARDS ATM USAGE AMONG SELECTED PRIVATE SECTOR BANKS IN COIMBATORE - .PA, PADMAAVATHY; RAMADEVI, V. (International Journal of Psychosocial Rehabilitation, 2020)
Convenience is the most significant advantage to buyers about going cashless. In fact, mobile payment applications have made it possible to complete a purchase without even having a credit card on hand. Paying with a card or smartphone comes with the convenience of having an electronic record of the transaction. Consumers often pay the price for such advantages. For example, there is greater temptation to overspend with a credit card since all purchases are buying presents, pay later. Also, taking MasterCard or charge data is substantially less complicated than making money. Going cashless has other, less immediately apparent financial liabilities. This study offers and validates an inclusive approach to explain the factors influencing the consumers’ preference towards the usage of ATM services by Retail customers among selected private sector banks in the Coimbatore city. In order to achieve these objectives, a sample of 1080 respondents who visited the select banks was drawn. Stratified proportionate random sampling method is used for selecting the respondents.